Struktur Anatomi Tiga Jenis Batang Rotan Anatomical Properties of Three Rattans Culm - Krisdianto Krisdianto; Jasni Jasni (Jurnal Ilmu dan Teknologi Kayu Tropis, 2005)
Rattan is one of the monocotyl species, which is economically important. Rattan culm is used for furniture, souvenir and housewares. Indonesian rattan varies accordingly, but only about 30% of them have been developed. This paper describes anatomical structure of three rattan species to get information about its utilization. Three rattan species namely Balubuk (Calamus burchianus Becc.), Lilin (Calamus javensis Bl.) and Tretes (Calamus heteroideus Bl.) were used as samples. Macroscopically, anatomical structure was observed on massive rattan culm, while microscopically was observed from microtome-sectioned samples. Fibre dimension was observed from macerated samples. All anatomical quantities were compared to those of Manau rattan, since its utilization has been known. The metaxylem diameter of those three rattans was bigger than that of Manau rattan, so that those rattans were less durable than Manau. Fibre of rattan studied was shorter and thinner than that of Manau, as a result their strength were lower than that of Manau rattan. As their strength were less than Manau, the utilization of these three species was not recommended to work on direct forces